The carriage of potentially pathogenic β-haemolytic streptococci (β-HS) in healthy adult inhabitants of Wielkopolska, Poland - Bura, Maciej; Michalak, Michał; Padzik, Magdalena; Gowin, Ewelina; Celczyńska-Bajew, Liliana; Mozer-Lisewska, Iwona (Family Medicine & Primary Care Review, 2016)
Background . Acute pharyngitis is a common disease in primary health care patients. Beta-hemolytic streptococci (β-HS ) are a frequent etiological agent, while swab culture from the throat and palatine tonsils is the gold standard for diagnosis. Objectives. The evaluation of the prevalence of potentially pathogenic β-HS carriage in young adult inhabitants of Wielkopolska. Material and methods. The study included 205 healthy young adult (18–44 years old) (29.0 ± 6.4) inhabitants (M – 95, F – 110) of Wielkopolska (Poland). Two swabs were taken from the throat: the first one was used to perform a rapid antigenic diagnostic test (RAD T) for group A streptococci (GAS ) and the second to grow a conventional culture. If β-HS grew, isolates were serotyped according to Lancefield. In addition, simple demographic and medical data were collected from the subjects. The study was financed from funds granted within the first edition of the “Give a hand” project (Karol Marcinkowski Poznan University of Medical Sciences). Results . Positive throat cultures were obtained in 15.6% out of 205 persons (n = 32). The distribution of β-HS serogroup results was as follows: group C (GCS ) – 17 cases (53.1% of cases where β-HS was positive), group F (GFS) – 9 cases (28.1%), GAS – 3 people (9.4%) and group G (GGS ) – 3 subjects (9.4%). The growth of the discussed bacteria in cultures was moderate or high in 53% of these cases. RAD T was positive in 5 cases (but only one person had GAS in throat culture). The positive culture result was significantly more frequent in men (62.5% out of 32 cases with β-HS growth, p = 0.0460). Conclusions . 1. The possibility of β-HS carriage must be taken into account when analysing the results of throat swab cultures. 2. GAS carriage is significantly lower than non-GAS carriage. 3. GCS were the most prevalent among non-GAS. 4. Being male may predispose individuals to β-HS carriage.